"This Isn't Who We Are": A Critical Discourse Analysis of School and District Leaders' Responses to Racial Violence. Issue 1 (January 2021) - Bridgeforth, James C.
Media reports have detailed the growing prevalence of incidents of racism and racial violence in K-12 schools and districts throughout the United States. The public nature of these incidents often requires a formal response from school and district leadership in the form of a press release, letter, or public statement. This study is an analysis of 140 press releases, emails, letters, and social media posts that educational leaders made in response to incidents of anti-Black racial violence occurring between 2014 and 2019. Using critical discourse analysis, the author finds that institutional leaders regularly responded to these incidents by prioritizing the reputation of the school or district, rather than the needs of the victims of racial violence. Leaders engaged in the organizational practice of institutional boundary making by positioning the incidents as unrepresentative of the larger community, instead of acknowledging the structural roots of anti-Blackness within their communities. Due to the endemic nature of anti-Black racism, the author argues that educational leaders must acknowledge the predictable nature of these incidents and proactively prepare to respond swiftly and decisively. Leaders' responses should be meaningful, action-oriented, and equity-minded, ultimately leading to organizational transformation, rather than simply protecting the image of the schools and districts that they lead.